Evaluasi Efektivitas Asesmen Kompetensi Madrasah Indonesia (AKMI) Dalam Mengukur Prestasi Siswa di MI Islamiyah Kambangan - Musyafak, Musyafak; Muslih, Moh.; Soebari, Titien Soewastiningsih (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to discuss the effectiveness of the Indonesian Madrasah Competency Assessment (AKMI) in the Kambangan Batang Madrasah Ibtidaiyah Salafiyah Unit. In this research, the method used is a qualitative method with a descriptive approach. The results of the research show that the effectiveness of the AKMI Policy in Madarasah Ibtidaiyah has been regulated in detail in the Standard Operating Procedures (POS) for the Implementation of the Indonesian Madrasah Competency Assessment (AKMI) in 2021 and 2022 which includes 17 (seventeen) points. The seventeen points are explained in detail from the introductory points to monitoring, evaluating and reporting on the implementation of AKMI. Next, evaluate the effectiveness of the Indonesian Madrasah Competency Assessment (AKMI) in measuring student achievement at MI Islamiyah Kambangan, namely all teachers so they can improve student competence by trying and finding new breakthroughs when learning. Madrasas still need improvement and other efforts to increase student competency. The level of assessment or competency status of students at AKMI and the aim of implementing AKMI is to measure madrasah students' competency in reading literacy, numeracy, science and socio-culture (Religious Moderation) as diagnostic data for follow-up actions to improve learning in madrasas.